Cognitive Function and Brain Atrophy Predict Non-pharmacological Efficacy in Dementia: The Mihama-Kiho Scan Project2 - Tabei, Ken-ichi; Satoh, Masayuki; Ogawa, Jun-ichi; Tokita, Tomoko; Nakaguchi, Noriko; Nakao, Koji; Kida, Hirotaka; Tomimoto, Hidekazu (Frontiers in Aging Neuroscience, 2018)
We aimed to determine whether neuropsychological deficits and brain atrophy could predict the efficacy of non-pharmacological interventions. Forty-six participants with mild-to-moderate dementia were monitored for 6 months; 25 underwent an intervention involving physical exercise with music, and 21 performed cognitive stimulation tasks. Participants were categorized into improvement and no-improvement subgroups. In the exercise-with-music group, the no-improvement subgroup performed worse than the improvement subgroup on the Rivermead Behavioural Memory Test at baseline. In the cognitive-stimulation group, the no-improvement subgroup performed worse than the improvement subgroup on Raven’s Colored Progressive Matrices and the cognitive functional independence measure at baseline. In the no-improvement subgroup, voxel-based morphometric analysis at baseline revealed more extensive gray matter loss in the anterior cingulate gyrus and left middle frontal gyrus in the exercise-with-music and cognitive-stimulation groups, respectively. Participants with mild-to-moderate dementia with cognitive decline and extensive cortical atrophy are less likely to show improved cognitive function after non-pharmaceutical therapy.